Anthropomorphic figurines from Vinča excavations 1998–2009 - Nenad Tasić (Documenta Praehistorica, 2011)
The paper presents figurines from excavations at Vinča 1998–2000 dated to the very end of the Late Neolithic. Along with a presentation and analysis of these objects, the paper addresses questions of the development of sculpture in Vinča, and matters of symbolism in the Late Vinča period. Some interesting contexts with an abundance of anthropomorphic figurines are presented and discussed.